2019
DOI: 10.1371/journal.pone.0215517
|View full text |Cite
|
Sign up to set email alerts
|

Attendance and compliance with an exercise program during localized breast cancer treatment in a randomized controlled trial: The PACT study

Abstract: Purpose Maintaining high adherence rates (session attendance and compliance) in exercise programs during breast cancer treatment can be challenging. We aimed to identify adherence rates and predictors to an exercise program during adjuvant breast cancer treatment. Methods Ninety-two patients with localized breast cancer undergoing chemotherapy were randomly assigned to an 18-week supervised moderate-to-high intensity aerobic and resistance exercise program, including tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 36 publications
8
48
2
4
Order By: Relevance
“…Again, this finding is consistent with trends in the general population, [59,60] as well as with a number of intervention studies that found that oncology patients with more education had higher rates of adherence with prescribed exercise regimens. [61][62][63] The complex relationship between education and health, often referred to as an education gradient, is partially explained by the idea that individuals with more years of education have higher incomes that provide increased access to resources (e.g., gym memberships); afford more time for health-related activities; and provide access to social networks that can amplify health behaviors like exercise. [60,64,65] This hypothesis is consistent with our findings that a significantly higher percentage of patients in the NoEx were less likely to be employed and reported a lower annual household income.…”
Section: Discussionmentioning
confidence: 99%
“…Again, this finding is consistent with trends in the general population, [59,60] as well as with a number of intervention studies that found that oncology patients with more education had higher rates of adherence with prescribed exercise regimens. [61][62][63] The complex relationship between education and health, often referred to as an education gradient, is partially explained by the idea that individuals with more years of education have higher incomes that provide increased access to resources (e.g., gym memberships); afford more time for health-related activities; and provide access to social networks that can amplify health behaviors like exercise. [60,64,65] This hypothesis is consistent with our findings that a significantly higher percentage of patients in the NoEx were less likely to be employed and reported a lower annual household income.…”
Section: Discussionmentioning
confidence: 99%
“…It was expressed both as attendance and compliance rates. 19 Attendance rates were computed for each patient as the number of sessions completed, divided by the number of planned sessions attended. Compliance rates were defined in terms of the duration and prescribed intensity of the aerobic training and were rated as the percentage of sessions performed reaching the goal of 30 minutes training (compliance with duration) and the percentage performed at an intensity between 64% and 76% of maximal heart rate (compliance with prescribed intensity).…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, a large portion of our study sample (nearly 40%) had elementary education or was illiterate. Since educational level was found to be a significant predictor for exercise compliance in cancer patients [ 51 ], a low level of education in a large portion of the patients may reduce the exercise compliance in the present study. Further studies are needed to investigate exercise compliance across patients with different sociodemographic characteristics.…”
Section: Discussionmentioning
confidence: 83%